Application of Environmental Education in Elementary School: Penerapan Pendidikan Lingkungan Hidup di Sekolah Dasar - Dia Nikmatus Solika; Mukhlasin Amrullah (Universitas Muhammadiyah Sidoarjo, 2022)
This qualitative study aims to investigate the planning and implementation of environmental education at SD Muhammadiyah 1 Krembung, as well as identify the obstacles encountered during the implementation process. The research subjects included teachers and students of the school. Data was collected through interviews, observation, and documentation, with data validity ensured through triangulation. The findings revealed that the planning of environmental education at SD Muhammadiyah 1 Krembung involved several steps, such as selecting appropriate learning materials, analyzing learning objectives, and conducting a goal analysis of environmental issues. The application of environmental education in the school followed the indicators set for environmental education in both the school and classroom settings. Most of these indicators were successfully realized, including fostering habits of maintaining and preserving the school environment, providing adequate garbage disposal and hand washing facilities, promoting energy-saving practices, encouraging waste separation between organic and non-organic materials, ensuring cleanliness through the provision of cleaning equipment, cultivating a sense of responsibility towards a clean environment, and maintaining evaluation tools. Additionally, a learning concept map oriented towards environmental education was developed. The results of this study have implications for enhancing the effectiveness of environmental education in schools, which can contribute to environmental awareness and action among students. Highlights: Importance of planning: Planning plays a crucial role in the successful implementation of environmental education, ensuring the selection of appropriate materials and analysis of learning objectives. Realization of indicators: The application of environmental education at SD Muhammadiyah 1 Krembung demonstrated the successful realization of indicators in promoting environmental awareness and action among students. Implications for effective education: The findings of this study have implications for enhancing the effectiveness of environmental education in schools, contributing to a cleaner and more sustainable environment. Keywords: Environmental education,environmental character care, qualitative research, implementation, obstacles.